(untitled) (Journal of Comparative & International Higher Education, 2024)
International students, especially Chinese international students, are underrepresented in leadership roles in Canadian universities. A review of the related literature indicates that low language proficiency, lack of belongingness, and cultural difference inhibited Chinese international students’ leadership opportunities. This study adopted semi-structured, one-on-one interviews to investigate the benefits that five Chinese international student participants perceived, based on leadership roles in which they participated. The results suggest that taking student leadership roles facilitated participants’ language development at one Canadian university and enhanced their belongingness to the university. However, their participation in student leadership roles did not contribute to their belongingness to Canadian society.